Heterogeneities of the perceptual-motor style during locomotion at height - Wang, Danping; Bargiotas, Ioannis; Cao, Jiuwen; Vayatis, Nicolas; Oudre, Laurent; Vidal, Pierre-Paul (Frontiers in Human Neuroscience, 2024)
Humans exhibit various perceptual motor styles. These styles reflect their intra- and inter-individual variability when they implement sensorimotor transformations. However, at what point should such perceptual motor styles be readjusted to maintain optimal motor control? Do changes in perceptual motor style reveal basic emotions? Do they reveal the onset of a pathology? Can they help in following rehabilitation and recovery? In a previous study (Mantilla et al. 2020), we investigated how to define the perceptual motor style of a healthy person when standing at rest and during locomotion. Our results suggested that the person’s perceptual motor style could be conveniently decomposed into a static component (a stable configuration of the various body segments with respect to the gravitational vertical) and dynamic components (head, trunk and limb movements). From there, we were able to identify static and dynamic markers that could specify the perceptual motor style of a person because they featured large inter-variability and low intra-individual variability. In this study, we aimed to investigate the modulation of the perceptual motor style during locomotion at a height in 16 individuals with no antecedent fear of height or acrophobia. We used a low-cost virtual reality (VR) video game. In this VR game, Richie's Plank, the person progresses on a narrow plank placed between two buildings at the height of the 30th floor. A surprising finding was the large heterogeneity of these changes in the 16 individuals we tested. Both static markers (stable configurations of the head, trunk and limbs with respect to the gravitational vertical) and dynamic markers (jerk, entropy, sample entropy, and the two-third power Law). In addition, 56 % of the participants showed persistent modification of at least one variables of their skeletal configuration and 61% of one variables of their dynamic control of locomotion on ground after being exposed to height.